Pembatasan Hak Akses Dengan Menggunakan Web Proxy Berbasis Mikrotik: Filtering Hak Akses Dengan Web Proxy - rani, Karisma Angeria; Walad Mahfuzhi, A.R. (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
Along with the rapid development of computer network technology, users can now access the network more quickly and efficiently. However, behind the ease of internet access, a new problem has emerged, namely the ease of accessing negative sites that are considered less useful for users. Some of these are pornographic sites, sites containing violent content, and increasingly gambling sites. This research aims to create a healthier internet by implementing restrictions on access rights on negative sites, limiting and controlling internet access, and increasing network security and efficiency to prevent misuse of access. The method used in this research is the Experiment Oriented method, which aims to test the implementation of a system for limiting access rights using MikroTik devices in computer networks. The stages of implementing this research include problem identification, design, implementation, and testing stages. The research results show that the implementation of a MikroTik-based web proxy in the Computer Laboratory of the Faculty of Engineering, Muhammadiyah University of Bengkulu is effective in improving network security. This web proxy succeeded in limiting access rights to 26 useless sites, such as pornography and gambling sites. Additionally, this configuration also helps limit access to sites that are not relevant to academic purposes, thereby creating a more secure and controlled network environment. Keywords— Access restrictions, web proxies, Negative Sites, Mikrotik and Network Security